Kajian Tingkat Kerawanan Erosi Tanah Berbasis Spasial dan Survei Lapangan di Kecamatan Tewah, Kabupaten Gunung Mas, Provinsi Kalimantan Tengah: Assessment Of Soil Erosion Vulnerability Level Based on Spatial and Field Survey In Tewah Sub-District, Gunung Mas Regency Central Kalimantan Province - Saputra, Jodi; Sukarna, Raden Mas; Junaedi, Ajun; Rizal, Moh (HUTAN TROPIKA, 2024)
This study aims to identify and map the level of soil erosion vulnerability in Tewah Sub District, Gunung Mas Regency, Central Kalimantan Province. Identification of the level of soil erosion vulnerability was carried out using parameters of slope, soil type, rainfall and land cover. Field surveys were conducted to collect data on the area of ​​tree canopy cover at each level of erosion vulnerability. The results of the study indicate that in Tewah Sub District, which is included in the Kahayan Sub-Watershed have 5 levels of soil erosion vulnerability with categories of not vulnerable, less vulnerable, quite vulnerable, vulnerable and very vulnerable. Furthermore, it is known that ±50.23% of the research location area is included in the category of quite vulnerable and only ±0.29% is included in the category of not vulnerable. The value of ​​tree canopy cover has a significant effect on the level of soil erosion vulnerability. The higher the area of ​​tree canopy cover, the lower the level of erosion vulnerability. Thus, it can be concluded that erosion vulnerability due to lack of forest cover, especially in Tewah Sub District, must be a priority in handling to support the carrying capacity of the environmental ecosystem.